A Comprehensive Review of Urticaria and Angioedema 2017
DOI: 10.5772/67713
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Prophylaxis in Odontostomatological, Maxillofacial and ENT Procedures in Patients with Hereditary Angioedema Due to C1‐Inhibitor Deficiency

Abstract: Oestrogens, trauma, infections or stress has been described as triggers for angioedema (AE) attacks in patients with hereditary angioedema due to C1-inhibitor deficiency (C1-INH-HAE). Microtrauma can precipitate the onset of acute AE attacks, and thus, dental-oral procedures carry a high risk of triggering them and also an increased risk of death from asphyxiation due to the AE location. In the past, without proper specific treatment, the overall mortality after dental surgery in patients with C1-INH-HAE was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Also Zanette in another study ( 2 ) showed how patients with systemic diseases have more anxiety than patients who are not systemically compromised. These have more risk of developing an acute attack during the perioperative phase because they already have preoperative anxiety ( 10 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also Zanette in another study ( 2 ) showed how patients with systemic diseases have more anxiety than patients who are not systemically compromised. These have more risk of developing an acute attack during the perioperative phase because they already have preoperative anxiety ( 10 12 ).…”
Section: Discussionmentioning
confidence: 99%